Unique Model of Criminal Record Management System in the Perspective of Somalia - Fowzi Jamal Mohamed Barrow; Mohammad Jahangir Alam; Md. Nurul Mustafa (JOIV : International Journal on Informatics Visualization, 2019)
The project Criminal Record Management System in the perspective of Somalia is a Criminal record management system that uses to record crime activities of criminals. It can be used to report criminal activities. This project is mainly useful for law and enforcement agencies in Somalia. The law and enforcement authority can preserve records of the criminals and search for any criminal using the system. This is an online web application with a database system in which police will keep the record of criminals who have been arrested.  We have used HTML, JavaScript, CSS, PHP, MySql and Bootstrap to develop this system.  We have also used binary search algorithm to find a criminal from the database. The project's interface is very user-friendly and helpful for authority.